The Application Of E-Government Through Online Services (PLAVON) DUKCAPIL (Case study In Kajeksan Village, Tulangan District, Sidoarjo Regency) - Ummaroh, Nur Azizatul; Choiriyah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2023)
This qualitative descriptive study aims to explore and describe the implementation of e-government through the use of the Pelayanan Via Online (PLAVON) system in Kajeksan Village, Tulangan Subdistrict, Sidoarjo Regency, Indonesia. The research employed a purposive sampling technique and utilized observations, interviews, and document analysis as data collection methods. Drawing on Indrajit's (2002) theory of e-government implementation, the study focused on three key indicators: legal infrastructure, human infrastructure, and technological infrastructure. The legal infrastructure was supported by the regulatory framework outlined in the Ministry of Home Affairs Regulation No. 7 of 2019 concerning online population administration services. Findings revealed that the implementation of the PLAVON system was effectively carried out in accordance with governmental regulations. However, challenges were identified in terms of public awareness and understanding of the PLAVON system, as well as difficulties in accessing the online services. The study highlights the importance of human infrastructure, emphasizing the need for enhanced knowledge and skills among government employees, as well as the provision of necessary technological facilities. The findings have implications for policymakers and stakeholders seeking to promote efficient and inclusive e-government services in rural communities. Highlights: Effective Implementation: The study showcases the successful implementation of the Pelayanan Via Online (PLAVON) system, emphasizing its compliance with legal regulations and governmental guidelines. Human Infrastructure Challenges: The research highlights the need for enhancing the knowledge and skills of government employees in utilizing the PLAVON system, while addressing the limited awareness and understanding among the local community. Technological Facilities: The study emphasizes the importance of providing necessary technological resources, such as laptops and printers, to enable smooth access and utilization of the PLAVON system in rural areas. Keywords: e-government, PLAVON system, rural communities, implementation, infrastructure.